2008
DOI: 10.1585/pfr.3.s1021
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Behavior of Drift Waves in LMD-U

Abstract: In the LMD-U linear magnetized plasma, fluctuation measurements have been performed with multi-channel poloidal Langmuir probe arrays to investigate the spatiotemporal behaviors of drift wave turbulence. Twodimensional (poloidal mode number-frequency) power spectrum showed not only fluctuation peaks but also the existence of a broadband fluctuation. The broadband fluctuation developed at high poloidal mode number and high frequency regions and not along the linear dispersion relation curve of drift wave modes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…By decreasing the neutral pressure, the turbulence regime changes to streamer-type structures. 29,30 A radially movable Mach probe is installed at h ¼ p/4, z ¼ 1.625 m, whose probe head can be scanned from r ¼ 2 cm (r/a ¼ 0.4) to r ¼ 6 cm (r/a ¼ 1.2) on a shot-to-shot basis. The diameter of the probe head is $5 mm, and the probe head houses four probe tips each of which are 0.5 mm in diameter.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…By decreasing the neutral pressure, the turbulence regime changes to streamer-type structures. 29,30 A radially movable Mach probe is installed at h ¼ p/4, z ¼ 1.625 m, whose probe head can be scanned from r ¼ 2 cm (r/a ¼ 0.4) to r ¼ 6 cm (r/a ¼ 1.2) on a shot-to-shot basis. The diameter of the probe head is $5 mm, and the probe head houses four probe tips each of which are 0.5 mm in diameter.…”
Section: Experimental Apparatusmentioning
confidence: 99%
“…For instance, in linear cylindrical devices, such as the Kiel Instruments for Wave Investigation (KIWI) [21] and the Large Mirror Device Upgrade (LMD-U) [22,23] and a toroidal device, TJ-K [24], the Langmuir probe arrays surrounding the plasma surface in the azimuthal direction are used to measure both the spatial and temporal evolution of fluctuations. Figure 3 (a) shows an example of 2D Fourier spectra, S (k θ , ω), measured with a 64 channel azimuthal probe array in an LMD-U linear cylindrical plasma [25][26][27]. Here, the power spectrum can be defined by the ensemble average of the auto-powers asS auto (k θ , ω) = |ũ(k θ , ω)| 2 .…”
Section: Full Spectral Decomposition Of Turbulence -Frequency and Wavmentioning
confidence: 99%
“…The envelope modulations of turbulent drift wave fluctuations are observed. Moreover, bispectral analysis is used to identify the mutual interaction of drift waves [9][10][11][12][13]. A convergence study of bispectral analysis results [14] has indicated that a large number of repetitions are required to obtain a precise value for the author's e-mail: kobayashi@riam.kyushu-u.ac.jp bicoherence.…”
Section: Introductionmentioning
confidence: 99%